Large-Scale Black Silicon Induced by Femtosecond Laser Assisted With Laser Cleaning - Wen, Zhidong; Shi, Haiyan; Yue, Song; Li, Man; Zhang, Zhe; Wang, Ran; Song, Qi; Xu, Ziye; Zhang, Zichen; Hou, Yu (Frontiers in Physics, 2022)
Black silicon is a promising and effective candidate in the field of photoelectric devices due to the high absorptance and broad-spectrum absorption property. The deposition around the processing area induced by the pressure of SF6, gravity, and the block of the processing chamber interferes the adjacent laser ablation and hampers uniform large-scale black silicon fabrication. To solve the problem, femtosecond laser- induced black silicon assisted with laser plasma shockwave cleaning is creatively proposed in our study. The results showed that higher, denser, and more uniform microstructures can be obtained than the conventional laser-induced method without laser cleaning. The average absorptance is 99.15% in the wavelength range of 0.3–2.5 µm, while it is more than 90% in the range of 2.5–20 µm. In addition, the scanning pitch dependence of surface morphology is discussed, and the better result is obtained in the range of 25–35 µm with 40-µm laser spot. Finally, a large-scale 50-mm × 50-mm black silicon with uniform microstructures was prepared by our method. It has been demonstrated that the deposition is effectively eliminated via our method, and the optical absorption is also enhanced significantly. It is of great significance for realizing large-scale preparation of photoelectric devices based on black silicon and lays the foundation for the development of laser-inducing equipment and industrial application.